Further Testing of Social Disorganization Theory: An Elaboration of Sampson and Groves's "Community Structure and Crime" - Veysey, Bonita M. (Journal of research in crime and delinquency, 1999)
In one of the more important studies in the criminological literature over the past decade, Sampson and Groves analyze data from 238 British neighborhoods to test the mediating effect of indicators of social disorganization variables on the relationship between structural community characteristics and crime. In this article, the authors recognize that advances in statistical theory and software allow for a more detailed analysis of Sampson and Groves's integrated theory of community-level social disorganization. Using covariance structure modeling (LISREL), the results of their analysis reveal that (1) Sampson and Groves's argument regarding the mediating effect of social disorganization variables is only partially supported, (2) social disorganization is not one construct but rather represents several mechanisms by which communities maintain stability, and (3) the resulting model may be interpreted as supportive of several theories of crime, including peer affiliation theories, as well as social disorganization